Clustering of Regencies and Municipalities Based on the Number of Livestock in East Java Province Using the Fuzzy C-Means Method - Salsabilla, Intan Agnesa (Primakara University, 2025)
This study was conducted to cluster regencies and municipalities in East Java Province based on the population of livestock, aiming to identify regional distribution patterns according to livestock characteristics. The clustering was performed using the Fuzzy C-Means algorithm and validated through the Partition Coefficient Index method. The implementation was carried out in a web-based application using the Laravel framework. The stages of this research included data collection, normalization, Fuzzy C-Means computation, evaluation using the Partition Coefficient Index, and profiling of cluster characteristics. The results of the study, tested with cluster numbers ranging from 2 to 10, indicated that the optimal number of clusters was two for both 2021 and 2022, with Partition Coefficient Index values of 0.7507 for 2021 and 0.7486 for 2022. In 2021, the optimal clustering produced Cluster 1consisting of 7 regencies and 9 cities, and Cluster 2 consisting of 22 regencies. In 2022, the optimal clustering resulted in Cluster 1 consisting of 21 regencies, and Cluster 2 consisting of 8 regencies and 9 cities.